2015
DOI: 10.1007/s40264-015-0269-9
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Effects of Fetal Antiepileptic Drug Exposure

Abstract: Many studies investigating cognitive outcomes in children of women with epilepsy report an increased risk of mental impairment. Verbal scores on neuropsychometric measures may be selectively more involved. While a variety of factors contribute to the cognitive problems of children of women with epilepsy, antiepileptic drugs (AEDs) appear to play a major role. The mechanisms by which AEDs affect neurodevelopmental outcomes remain poorly defined. Animal models suggest that AED-induced apoptosis, altered neurotra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 53 publications
1
29
1
Order By: Relevance
“…attention. In line with earlier studies on older children [5,10,14,26,27,58], we found prenatal AED exposure to compromise the development of early language and social skills, as well as overall neurodevelopment at the age of seven months. However, our eye-tracker-based assessment suggests that the general speed of visuospatial orienting (or "disengagement") as well as attentional bias for faces is spared at the age of seven months in infants with prenatal AED exposure.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…attention. In line with earlier studies on older children [5,10,14,26,27,58], we found prenatal AED exposure to compromise the development of early language and social skills, as well as overall neurodevelopment at the age of seven months. However, our eye-tracker-based assessment suggests that the general speed of visuospatial orienting (or "disengagement") as well as attentional bias for faces is spared at the age of seven months in infants with prenatal AED exposure.…”
Section: Discussionsupporting
confidence: 91%
“…Besides the need for assessing the general effects of AED exposure on early development [7,9,10,[25][26][27], it has become important to assess changes in specific cognitive processes, and in particular, those related to visual functions. Recent developments in eye-tracking-based testing of infant cognition [28][29][30] have opened new possibilities for automated testing of infants' visual acuity, visuospatial orienting (gaze shifts to a novel visual stimulus), and attention to salient social stimuli, such as faces [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…The estimated risk of neural tube defects, mostly spina bifida, is 0.5-1 % [33]. Studies on poor cognitive outcomes in offspring of mothers treated with CBZ show contradictory results, but most suggest that major poor cognitive outcomes should not be attributed to exposure to CBZ [34].…”
Section: Carbamazepine and Oxcarbazepinementioning
confidence: 99%
“…Lamotrigine is associated with a 10-24-fold risk of oral cleft versus the general population [44]. So far, most of the investigations available suggest that fetal exposures to LMT are safer with regard to cognition when compared with other antiepileptic drugs [34].…”
Section: Lamotriginementioning
confidence: 99%
“…For example, fetal valproate exposure causes dose-dependent reduction of cognitive abilities, and these appear to persist at least until the age of 6 [1]. Bittigau et al [2] reported that exposure to therapeutic levels of AEDs induced neuronal apoptosis in rat brains during the first 2 post-natal weeks.…”
Section: Introductionmentioning
confidence: 99%